(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research examines media coverage in Myanmar in 2009 via a Critical Discourse Analysis (CDA), with a focus on articles published in the "7 Day Weekly Journal" from February to December 2009. The media's portrayal of different democratic ideals and dictatorship ideologies is analyzed in this study. Topics covered in the study include popular sovereignty, political equality, rule of law, pluralism, political freedom, transparency and accountability, civil liberties, and authoritarian ideas such as centralized power, suppression of opposition, controlled participation and propaganda, restrictions on civil liberties, rule by decree and weak rule of law, cult of personality, use of force, corruption, and nepotism. The purpose of this study is to use CDA to examine how the articles published in the "7 Day Weekly Journal" between February and December present and frame democratic values and authoritarian ideologies. Furthermore, using Critical Discourse Analysis as a prism, it assesses how the media in Myanmar impacted public opinion and political debate prior to 2009. Results show how Myanmar’s media steered clear of authoritarian governments and toward democratic principles in the country's complicated political climate. This study sheds light on a pivotal era in Myanmar's political history by demonstrating how the media influenced popular opinion and political debate.